Implementasi Six Sigma pada Sistem Pembelian, Persediaan dan Distribusi Bahan Baku atau Barang Jadi pada PT XYZ - Novianty Novianty; Hadi Santoso; Hartono Hartono (LPPM Universitas Widya Dharma Pontianak, 2022)
The purpose of this study is to prove that problems in the purchasing, inventory and distribution system of raw materials or finished goods at PT XYZ can be resolved through the implementation of the Six Sigma project. This is because there are many problems in purchasing errors of goods ordered not according to specifications, errors or delays in inputting purchase and inventory data, many raw materials or finished goods are damaged in the warehouse while procurement continues to purchase goods without checking the availability of goods in the warehouse, frequent theft goods in warehouses, and so on. The form of this research is a descriptive study with a survey method. Data collection techniques used were interviews, observation and documentary studies. The data analysis technique used is to analyze the initial conditions of the purchasing, inventory and distribution system of raw materials or finished goods before the company applies the Six Sigma concept. The next process is to analyze the six sigma implementation process in the purchasing, inventory and distribution system of raw materials or finished goods by describing the root causes, causes, effects and solutions or action plans. The last stage is analyzing the impact of the implementation of the six sigma concept. The conclusion in this study is that the company gets fairly optimal results in the form of cost savings, prevention of purchases outside the company, can utilize warehouse stock, apply the principle of 5 R in the warehouse, and prevent theft in the warehouse. The implementation of the Six Sigma project is expected to continue so that it can help company management realize the company's vision and mission. The author's suggestion is that company management should remain consistent and exercise control over the implementation of the Six Sigma project in the purchasing, inventory and distribution system of raw materials or goods.Keywords: six sigma, purchasing system, inventory and distribution system of raw materials or goods.